Phytochemical composition and bioactivity of Debregeasia saeneb leaves: Insights into anti-diabetic and antioxidant properties - Rashid Khan; Rabia Afza; Bashir Ahmad; Sumaira Miskeen; Khalid Ahmad; Mostafa A. Abdel-Maksoud; Salman Alrokayan; Mohamed Y. Zaky (PLoS ONE, 2025)
Medicinal plants are an essential reservoir of natural compounds with diverse pharmacological properties. This study focuses on Debregeasia saeneb, (Forsk.) Hepper & J.R.I.Wood a relatively unexplored plant recognized for its traditional medicinal uses. The research aims to identify and analyze the phytochemical composition of D. saeneb (Forsk.) Hepper & J.R.I.Wood leaves, as well as evaluating their antioxidant and antidiabetic potential. This study systematically identified and analyzed the phytochemical constituents of D. saeneb (Forsk.) Hepper & J.R.I.Wood leaves utilizing Gas Chromatography-Mass Spectrometry (GC-MS), alongside both quantitative and qualitative assays. The biological activities were assessed through radical scavenging assays, specifically DPPH (1,1-di-phenyl-2-picrylhydrazyl), ABTS (2,2-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)), and α-amylase inhibitory assays, which have been largely underexplored across various solvents. The GC-MS analysis revealed a diverse range of compounds, with ethyl acetate extracts containing six compounds, chloroform extracts containing seven, and n-hexane extracts containing three distinct compounds. Further qualitative assessments confirmed the presence of glycosides, leucoanthocyanins, quinones, lignins, carbohydrates, terpenoids, anthraquinones, and phlobatannins in the extracts of D. saeneb (Forsk.) Hepper & J.R.I.Wood. Quantitative analyses established the total phenolic, tannin, and flavonoid contents, revealing a positive correlation among the different extracts. Specifically, the total flavonoid (TF) content in the standard ranged from 0.34 to 1.189 µg/mL, while in methanol extracts it ranged from 0.087 to 0.778 µg/mL, in ethyl acetate from 0.188 to 0.624 µg/mL, and in n-hexane from 0.03 to 0.44 µg/mL. The total tannin content (TTC) in the standard ranged from 0.462 to 2.359 µg/mL, with methanol extracts showing values from 0.016 to 0.048 µg/mL, ethyl acetate from 0.0196 to 0.153 µg/mL, and n-hexane from 0.0012 to 0.134 µg/mL. The total phenolic content (TPC) in the standard ranged from 0.11 to 0.38 µg/mL, with methanol extracts ranging from 0.042 to 0.267 µg/mL, ethyl acetate from 0.0275 to 0.487 µg/mL, and n-hexane from 0.001 to 0.348 µg/mL. In ethanol extracts, the radical scavenging capacity (RSC) ranged from 0.005 to 0.05 µg/mL, in methanol from 0.01 to 0.09 µg/mL, and in aqueous extracts from 0.005 to 0.035 µg/mL, while the standard RSC ranged from 0.5 to 4.5 µg/mL. The biological activity assays indicated that D. saeneb (Forsk.) Hepper & J.R.I.Wood extracts exhibited significant α-amylase inhibition, suggesting potential anti-diabetic properties. Furthermore, all extracts demonstrated radical scavenging activity in both ABTS and DPPH assays, with the methanol extract exhibiting the highest antioxidant activity. In conclusion, this research provides comprehensive insights into the phytochemical profile of D. saeneb (Forsk.) Hepper & J.R.I.Wood leaves and its potential therapeutic applications, including anti-diabetic and antioxidant effects, thereby warranting further investigation into molecular mechanisms, drug development, and health promotion.